The teaching and learning of Arabic in early modern Europe - Loop, Jan.; Hamilton, Alastair, 1941-; Burnett, Charles (The History of Oriental Studies, 2017)
This volume brings together the leading experts in the history of European Oriental Studies. Their essays present a comprehensive history of the teaching and learning of Arabic in early modern Europe, covering a wide geographical area from southern to northern Europe and discussing the many ways and purposes for which the Arabic language was taught and studied by scholars, theologians, merchants, diplomats and prisoners. The contributions shed light on different methods and contents of language teaching in a variety of academic, scholarly and missionary contexts in the Protestant and the Roman Catholic world. But they also look beyond the institutional history of Arabic studies and consider the importance of alternative ways in which the study of Arabic was persued. Contributors are Asaph Ben Tov, Maurits H. van den Boogert, Sonja Brentjes, Mordechai Feingold, Mercedes García-Arenal, John-Paul A. Ghobrial, Aurélien Girard, Alastair Hamilton, Jan Loop, Nuria Martínez de Castilla Muñoz, Simon Mills, Fernando Rodríguez Mediano, Bernd Roling, Arnoud Vrolijk. This title, in its entirety, is available online in Open Access.